Stochastic study on effects of material and physical parameters on slow crack growth behaviors of HDPE using the crack layer theory. (15th June 2020) - Wee, Jung-Wook; Choi, Byoung-Ho
Highlights: Variation of crack layer parameters on slow crack growth is investigated. Stochastic slow crack growth kinetics of HDPE is analyzed. Lifetime distribution was fitted by two probability distribution functions. Regression model of key parameters of the probability distribution function was evaluated. Abstract: High-density polyethylene exhibits discontinuous slow crack growth (SCG) mode in fatigue and creep conditions. To simulate the unique SCG mode, the crack layer (CL) theory can be adopted as an alternative method. However, the stochastic approach is also required for reliability-related problems. In this study, the current deterministic CL model was modified to describe the stochastic discontinuous SCG. First, the influence of the normally distributed nine input parameters in CL simulation on discontinuous SCG kinetics and the resulting lifetime distributions were thoroughly investigated. Second, important CL parameters that affect discontinuous SCG kinetics and the final lifetimes were identified. Then, the 2- and 3-parameter Weibull function and the Birnbaum–Saunders (B–S) function were compared to determine the function that correctly fits the lifetime distribution from discontinuous SCG. Finally, appropriate equations of the scale and shape parameters of the B–S function were developed with regard to the identified parameters.